1987
DOI: 10.1136/jnnp.50.10.1274
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a bimanual load-lifting task by parkinsonian patients.

Abstract: SUMMARY Normal subjects and Parkinsonian patients performed a bimanual load lifting task. In this task, one "postural" forearm, held in a horizontal position while supporting a 1 kg weight, was unloaded either by the experimenter's hand (imposed unloading) or by the subject's other hand in response to a tone burst (voluntary unloading). The variables recorded were reaction time (RT: time interval between the tone and beginning of unloading) and movement time (MT: duration of the change in force measured by a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(28 citation statements)
references
References 22 publications
3
25
0
Order By: Relevance
“…For the purpose of comparing our results with findings from previous studies, the first EMG burst in the unloading arm was used as the onset of unloading. This is in agreement with previous studies that show the mean movement time to lift a 1-kg weight completely off a force-sensing device is about 200 ms (Viallet et al, 1987(Viallet et al, , 1992 and that the onsets of EMG activity in the unloading arm occurred quasisynchronously with the instance of transient load change (Massion, Ioffe, Schmitz, Vialett, & Gantcheva, 1999;Forget & Lamarre, 1989;Massion et al, 1998). However, the same shift would be inappropriate for the imposed condition because the latency of the unloading reflex in the arm is in the order of 50 ms (Hugon et al, 1987;Schmitz et al, 2002;Forget & Lamarre, 1989).…”
Section: Emg Datasupporting
confidence: 93%
See 1 more Smart Citation
“…For the purpose of comparing our results with findings from previous studies, the first EMG burst in the unloading arm was used as the onset of unloading. This is in agreement with previous studies that show the mean movement time to lift a 1-kg weight completely off a force-sensing device is about 200 ms (Viallet et al, 1987(Viallet et al, , 1992 and that the onsets of EMG activity in the unloading arm occurred quasisynchronously with the instance of transient load change (Massion, Ioffe, Schmitz, Vialett, & Gantcheva, 1999;Forget & Lamarre, 1989;Massion et al, 1998). However, the same shift would be inappropriate for the imposed condition because the latency of the unloading reflex in the arm is in the order of 50 ms (Hugon et al, 1987;Schmitz et al, 2002;Forget & Lamarre, 1989).…”
Section: Emg Datasupporting
confidence: 93%
“…Apart from cortical lesions, pathology of subcortical structures including basal ganglia also affects postural adjustment in goal-directed movements. In two studies of patients with Parkinson's disease, the APA was partially preserved in half the patient group and abolished in the rest (Traub, Rothwell, & Marsden, 1980;Viallet, Massion, Massarino, & Khalil, 1987). In another study of patients with cerebellar pathology, APA was found to be largely intact, albeit with an onset significantly earlier relative to normal controls (Diedrichsen, Verstynen, Lehman, & Ivry, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…Severe APA impairments in patients with Parkinson's disease suggested a role of the basal ganglia in the anticipatory postural control (Viallet et al 1987). In particular, beyond their role in shaping the movement, basal ganglia may be involved in the intentional movement selection, through the pathway involving the anterior mid-circulates cortex (see Hoffstaedter et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Preparation for an action is of a major importance for various everyday actions. It has been shown to suffer in certain neurological conditions such as Parkinson's disease (Bazalgette et al 1986;Viallet et al 1987) and during normal aging (Woollacott et al 1988). We believe that studies of anticipatory covariation in different subpopulations can reveal changes that may be causally related to impairments in motor synergies.…”
Section: Concluding Comments and Limitations Of The Studymentioning
confidence: 99%